Fe-based alloy shapes

JP7629690B2Active Publication Date: 2025-02-14SANYO SPECIAL STEEL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020039871
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-09
Publication Date
2025-02-14
Estimated Expiration
2040-03-09

AI Technical Summary

Benefits of technology

【0020】 本発明に係るFe基合金造形物は、強度及び靱性に優れている。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629690000003
    Figure 0007629690000003
  • Figure 0007629690000004
    Figure 0007629690000004
  • Figure 0007629690000005
    Figure 0007629690000005
Patent Text Reader

Abstract

To provide an Fe-based alloy molding excellent in the strength and toughness.SOLUTION: A material of the Fe-based alloy molding is Fe based alloy. The Fe-based alloy includes Mo and Co of 0.0 mass% or larger and 0.5 mass% or smaller. The longitudinal length of the Laves phase derived from Fe2Mo phase in the metal structure of the Fe based-alloy molding is smaller than 450 nm. Preferably, the peak intensity I1(2θ=36.5±1°), the peak intensity I2(2θ=37.8±1°), the peak intensity I3(2θ=41.3±1°) and the background peak intensity I4 (2θ=35.0±1°) in the XRD diffraction pattern satisfy numerical formula (1): (I2-I4) / (I1-I4)≤1.5 and the numerical formula (2): (I3-I4) / (I1-I4)≤1.5.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an Fe-based alloy shaped article. In particular, the present invention relates to an Fe-based alloy shaped article produced by a rapid melting and rapid solidification process such as a three-dimensional additive manufacturing method, a thermal spraying method, a laser coating method, or a cladding method. [Background technology]

[0002] 3D printers are used to create metal objects. These 3D printers create objects using the additive manufacturing process. In additive manufacturing, a spread metal powder is irradiated with a laser beam or electron beam. The irradiation melts the metal particles of the powder. The particles then solidify. This melting and solidification causes the particles to bond together. Irradiation is selectively applied to parts of the metal powder. The parts of the powder that are not irradiated do not melt. A bonding layer is formed only in the irradiated parts.

[0003] A metal powder is then laid on top of the bonding layer. A laser beam or an electron beam is irradiated onto the metal powder. The irradiation melts the metal particles. The metal then solidifies. This melting and solidification bonds the particles in the powder together, forming a new bonding layer. The new bonding layer also bonds with the existing bonding layer.

[0004] By repeating the bonding by irradiation, an aggregate of bonding layers gradually grows. This growth results in a three-dimensional object. By the additive manufacturing method, objects with complex shapes can be easily obtained. An example of the additive manufacturing method is disclosed in Japanese Patent No. 4661842.

[0005] Alloys for aircraft and space structures require strength and fatigue resistance. Maraging steels are suitable for such applications.

[0006] JP 2013-253277 A discloses a maraging steel whose main component is Fe and which also contains Ni, Co, and Mo. The content of Co in this maraging steel is 7 mass% or more. This maraging steel contains W. This maraging steel does not contain Ti.

[0007] JP 2008-185183 A discloses a maraging steel containing Ni, Cr, Mo and Co. This maraging steel is subjected to a nitriding treatment. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent No. 4661842 [Patent Document 2] JP2013-253277A [Patent Document 3] JP2008-185183A Summary of the Invention [Problem to be solved by the invention]

[0009] In additive manufacturing, metal materials are rapidly melted and then rapidly cooled and solidified. Conventional maraging steel is not suitable as a material for objects manufactured using such a process involving rapid melting, rapid cooling and solidification.

[0010] A typical maraging steel contains substantially no C and alloy elements such as Ni, Mo, Ti, and Co. In this maraging steel, intermetallic compounds such as Ni3Mo and Ni3Ti phases are precipitated in the martensite matrix. These intermetallic compounds contribute to the high hardness and strength of objects made of the maraging steel.

[0011] Co lowers the solid solubility limit of Mo. Therefore, martensite with a large amount of Co added also has a large amount of supersaturated Mo. The addition of Co promotes the precipitation of the Ni3Mo phase in martensite.

[0012] On the other hand, since Co is an austenite-forming element, the addition of a large amount of Co inhibits martensitic transformation. The addition of a large amount of Co promotes the formation of μ-phase or σ-phase, which leads to embrittlement of the alloy. Furthermore, Co is subject to the Regulation on Prevention of Harm from Specified Chemical Substances, and from the viewpoint of compliance with this regulation, the addition of a large amount of Co to Fe is not preferable. For these reasons, it is preferable to suppress the amount of Co added. However, in steel with a suppressed amount of Co added, the Ni3Mo phase is difficult to precipitate. The mechanical properties such as hardness and strength of molded objects made of this steel are insufficient.

[0013] There is still room for improvement in the mechanical properties of additively manufactured objects made of Fe-based alloys. No Fe-based alloy objects that have excellent mechanical properties and can be obtained by rapid melting and rapid solidification processes such as thermal spraying, laser coating, and cladding have been proposed yet.

[0014] An object of the present invention is to provide an Fe-based alloy shaped article having excellent mechanical properties. [Means for solving the problem]

[0015] As a result of intensive research, the inventors have found that the Laves phase derived from the Fe2Mo phase precipitated in the metal structure of the shaped product affects the mechanical properties of the shaped product. They have also found that the formation of a metal structure that does not contain a coarse Laves phase compensates for the small amount of Co added and improves the mechanical properties of the Fe-based alloy shaped product, thereby completing the present invention.

[0016] That is, the material of the shaped article according to the present invention is an Fe-based alloy. This Fe-based alloy contains Mo and 0.0 mass % or more and 0.5 mass % or less of Co. In the metal structure of this shaped article, the length of the Laves phase derived from the Fe2Mo phase in the longitudinal direction is less than 450 nm. Preferably, the length of this Laves phase in the longitudinal direction is less than 100 nm.

[0017] Preferably, in a diffraction pattern obtained by XRD measurement of this Fe-based alloy shaped object, a peak intensity I1 at 2θ=36.5±1°, a peak intensity I2 at 2θ=37.8±1°, a peak intensity I3 at 2θ=41.3±1°, and a background peak intensity I4 at 2θ=35.0±1° satisfy the following mathematical expressions (1) and (2). (I2-I4) / (I1-I4)≦1.5 (1) (I3-I4) / (I1-I4)≦1.5 (2)

[0018] Preferably, in a diffraction pattern obtained by XRD measurement of this Fe-based alloy shaped object, a peak intensity I1 at 2θ=36.5±1°, a peak intensity I2 at 2θ=37.8±1°, a peak intensity I3 at 2θ=41.3±1°, and a background peak intensity I4 at 2θ=35.0±1° satisfy the following mathematical expressions (3) and (4). (I2-I4) / (I1-I4)≦1.0 (3) (I3-I4) / (I1-I4)≦1.0 (4)

[0019] Preferably, the Co content in the Fe-based alloy is less than 0.35 mass %. Effect of the Invention

[0020] The Fe-based alloy shaped article according to the present invention has excellent strength and toughness. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a transmission electron microscope image showing the metal structure of an Fe-based alloy shaped article according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a transmission electron microscope image showing the metal structure of the molded object of the comparative example. [Diagram 3] FIG. 3 shows an XRD diffraction pattern obtained for an Fe-based alloy shaped article according to one embodiment of the present invention. [Figure 4] FIG. 4 shows an XRD diffraction pattern obtained for the comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present invention will be described in detail below based on preferred embodiments. In this specification, unless otherwise specified, "X to Y" indicating a range means "X or more and Y or less." In addition, when the lower limit of the content of the component composition of an Fe-based alloy is described as "0.0 mass %, it means that the specified component (element) is not contained or is below the quantification limit.

[0023] The Fe-based alloy shaped product (hereinafter sometimes referred to as "shaped product") according to the present invention is produced by a process involving rapid melting, rapid cooling and solidification using Fe-based alloy powder (hereinafter sometimes referred to as "alloy powder"). The material of this shaped product is an Fe-based alloy. Preferably, the matrix structure of this shaped product is martensite. Depending on the shaping conditions, this shaped product may contain a structure other than martensite. Examples of structures other than martensite include austenite, bainite, etc.

[0024] The Fe-based alloy, which is the material of this shaped object, contains Mo and 0.0% by mass or more and 0.5% by mass or less of Co. Preferably, this Fe-based alloy further contains Ni, Ti, and Al. The main component of this Fe-based alloy is Fe. This Fe-based alloy may contain unavoidable impurities. The role of each element in this alloy will be described in detail below.

[0025] [Cobalt (Co)] As mentioned above, a large amount of Co inhibits martensitic transformation. In the shaped object according to the present invention, the Fe-based alloy, which is the material thereof, is set to a composition that does not contain Co, or if it does contain Co, the content is set to 0.5 mass% or less. The Co content in the Fe-based alloy is preferably as low as possible, more preferably 0.2 mass% or less, and even more preferably 0.1 mass% or less. The Co content may be substantially zero. Note that even if Co is not intentionally added, a small amount of Co may be inevitably contained in the alloy.

[0026] [Molybdenum (Mo)] In Fe-based alloys, Mo forms intermetallic compounds with Fe. A typical intermetallic compound is Fe2Mo. In Fe-based alloys that also contain Ni, Mo also forms intermetallic compounds with Ni. A typical intermetallic compound is Ni3Mo. These intermetallic compounds strengthen the Fe-based alloy. Shaped objects made of this Fe-based alloy have excellent strength, even though they are subjected to a rapid melting and rapid solidification process.

[0027] [Nickel (Ni)] In an Fe-based alloy containing Mo, Ni, Ti, and Al, Ni forms intermetallic compounds with Mo, Ti, and Al, respectively. Specific examples of intermetallic compounds are Ni3Mo, Ni3Ti, and Ni3Al. These intermetallic compounds strengthen the Fe-based alloy. Shaped objects made of this Fe-based alloy have excellent strength, even though they are subjected to a rapid melting and rapid solidification process.

[0028] [Titanium (Ti)] In Fe-based alloys containing Mo, Ni, Ti, and Al, Ti forms an intermetallic compound with Ni. A typical intermetallic compound is Ni3Ti. This intermetallic compound contributes to the creep rupture strength of Fe-based alloys. This intermetallic compound also contributes to the oxidation resistance of Fe-based alloys. Shaped objects made of this Fe-based alloy have excellent strength and durability despite being subjected to a rapid melting and rapid solidification process.

[0029] [Aluminum (Al)] In Fe-based alloys containing Mo, Ni, Ti, and Al, Al forms an intermetallic compound with Ni. A typical intermetallic compound is Ni3Al. This intermetallic compound contributes to the creep rupture strength of the Fe-based alloy. This intermetallic compound also contributes to the oxidation resistance of the alloy. Shaped objects made of this Fe-based alloy have excellent strength and durability, even though they are subjected to a rapid melting and rapid solidification process.

[0030] [molding] Preferably, the Fe-based alloy shaped article is (1) preparing an Fe-based alloy powder; and (2) The Fe-based alloy powder is melted and solidified to obtain an unheated molded object. The Fe-based alloy powder is composed of a large number of particles. The process for melting and solidifying the alloy powder includes a rapid melting and rapid solidification process. Specific examples of this process include a three-dimensional additive manufacturing method, a thermal spraying method, a laser coating method, and a cladding method. The three-dimensional additive manufacturing method is preferred.

[0031] A 3D printer can be used for this three-dimensional additive manufacturing method. In this additive manufacturing method, a laser beam or an electron beam is irradiated onto the spread alloy powder. The particles of the alloy powder are rapidly heated and melted by the irradiation. The particles then rapidly solidify. This melting and solidification causes the particles to bond together. Irradiation is selectively performed on a portion of the alloy powder. The parts of the alloy powder that are not irradiated do not melt. A bonding layer is formed only in the irradiated parts.

[0032] An alloy powder is further spread on the bonding layer. The alloy powder is irradiated with a laser beam or an electron beam. The particles are rapidly melted by the irradiation. The particles are then rapidly solidified. This melting and solidification bonds the particles in the alloy powder to each other, forming a new bonding layer. The new bonding layer also bonds with the existing bonding layer.

[0033] By repeating the bonding by irradiation, the aggregate of bonding layers gradually grows. This growth results in a three-dimensional object. This additive manufacturing method makes it easy to obtain objects with complex shapes.

[0034] [Hardness of unheated objects] The Rockwell hardness HRC of the shaped object after shaping, in other words before heat treatment, is preferably 30 or more and 40 or less. An unheat-treated shaped object having a Rockwell hardness HRC of 30 or more can provide an object with excellent strength. From this viewpoint, the Rockwell hardness HRC of the unheat-treated shaped object is particularly preferably 32 or more. An unheat-treated shaped object having a Rockwell hardness HRC of 40 or less has few internal defects such as cracks. From this viewpoint, the Rockwell hardness HRC of the unheat-treated shaped object is particularly preferably 38 or less. A method for measuring the Rockwell hardness HRC will be described later in the examples.

[0035] [Structure of unheat-treated object] The Laves phase derived from the intermetallic compound Fe2Mo may precipitate in the metal structure of a shaped product made of an Fe-based alloy containing Mo. The coarse Laves phase may impair the toughness of the Fe-based alloy. After shaping, in other words, before heat treatment, the Laves phase derived from the Fe2Mo phase contained in the metal structure of the shaped product preferably has a longitudinal length of less than 450 nm. A shaped product in which the longitudinal length of this Laves phase is less than 450 nm has excellent toughness. From this viewpoint, it is particularly preferable that the longitudinal length of the Laves phase is 100 nm or less. A method for measuring the Laves phase will be described later in the examples.

[0036] The Laves phase derived from the Fe2Mo phase precipitated in the metal structure is decomposed or refined by the heat treatment described below. Therefore, when the metal structure of an as-heat-treated shaped object after shaping contains a Laves phase having a longitudinal length of 450 nm or more, the Fe-based shaped object according to the present invention can be obtained by carrying out the heat treatment.

[0037] [XRD diffraction pattern of unheat-treated object] In the diffraction pattern obtained by performing XRD measurement on the shaped object after shaping, in other words before heat treatment, it is preferable that the peak intensity I1 at 2θ=36.5±1°, the peak intensity I2 at 2θ=37.8±1°, the peak intensity I3 at 2θ=41.3±1°, and the background peak intensity I4 at 2θ=35.0±1° satisfy the following formulas (1) and (2). A shaped object with excellent toughness can be obtained from an unheat-treated shaped object that satisfies formulas (1) and (2). (I2-I4) / (I1-I4)≦1.5 (1) (I3-I4) / (I1-I4)≦1.5 (2)

[0038] Here, the peaks at 2θ=37.8±1° and 2θ=41.3±1° are both diffraction peaks due to the Laves phase derived from the Fe2Mo phase. The peak at 2θ=36.5±1° is a diffraction peak due to the precipitation strengthening phase. The precipitation strengthening phase is a phase that precipitates during shaping, originating from an intermetallic compound (TiN) that contributes to improving the strength of the Fe-based alloy. Details of the XRD measurement will be described later in the examples.

[0039] From the viewpoint of improving toughness, it is more preferable that the above-mentioned peak strengths I1, I2, I3 and I4 satisfy the following formulas (3) and (4). (I2-I4) / (I1-I4)≦1.0 (3) (I3-I4) / (I1-I4)≦1.0 (4)

[0040] The Laves phase derived from the Fe2Mo phase precipitated in the metal structure is decomposed or refined by heat treatment, which will be described later. Therefore, when the diffraction pattern of an unheat-treated shaped object does not satisfy the above formulas (1) and (2) or formulas (3) and (4) after shaping, a Fe-based shaped object that satisfies the above formulas (1) and (2) or formulas (3) and (4) can be obtained by carrying out heat treatment.

[0041] [Martensitic transformation start temperature of unheat-treated objects] A shaped object having a martensitic transformation start temperature of 120°C or higher and 180°C or lower after shaping, in other words before heat treatment, is preferred. A shaped object having a martensitic transformation start temperature of 120°C or higher has a low content of Ni, which is an austenite forming element. Therefore, the martensitic transformation of this shaped object is not inhibited by Ni. From this viewpoint, the martensitic transformation start temperature of an unheat-treated shaped object is particularly preferably 130°C or higher. A shaped object having a martensitic transformation start temperature of 180°C or lower is likely to release internal stress during shaping, and therefore is less likely to develop internal cracks. From this viewpoint, the martensitic transformation start temperature of an unheat-treated shaped object is particularly preferably 170°C or lower. A method for measuring the martensitic transformation start temperature will be described later in the examples.

[0042] [Heat treatment] This Fe-based alloy molded object is (3) A step of subjecting the unheat-treated object obtained in the above step (2) to a heat treatment to obtain a shaped object. The Fe-based alloy shaped article may be obtained by a production method further comprising the steps of: (3-1) The process of subjecting unheat-treated objects to solution treatment and (3-2) Aging process for unheated objects In the above step (3-1) or (3-2), the unheat-treated shaped object preferably has a martensitic transformation start temperature of 120° C. or higher and 180° C. or lower.

[0043] In addition, when a process involving rapid melting and rapid solidification is performed as the above step (2), the effect of the solution heat treatment can be obtained after shaping, in other words, without heat treatment. Therefore, it is possible to omit the step (3-1). Step (3-1) may be performed after the step (2) using a process involving rapid melting and rapid solidification.

[0044] The solution heat treatment produces a supersaturated martensite structure. The aging heat treatment produces the precipitation of Ni3Mo, Ni3Ti, and Ni3Al in the martensite matrix. The precipitation of these intermetallic compounds produces an Fe-based alloy product with excellent strength and toughness.

[0045] The solution treatment temperature is preferably 700°C or higher and 1000°C or lower. A martensite structure in which alloy elements are sufficiently dissolved can be obtained by solution treatment at a temperature of 700°C or higher. From this viewpoint, the solution treatment temperature is more preferably 730°C or higher, and particularly preferably 750°C or higher. A solution treatment at a temperature of 1000°C or lower suppresses embrittlement of the structure. From this viewpoint, the solution treatment temperature is more preferably 970°C or lower, and particularly preferably 950°C or lower.

[0046] The solution treatment time is preferably 1.0 hour or more and 3.0 hours or less. A martensite structure in which alloy elements are sufficiently dissolved can be obtained by a solution treatment time of 1.0 hour or more. From this viewpoint, the solution treatment time is more preferably 1.3 hours or more, and particularly preferably 1.5 hours or more. A solution treatment time of 3.0 hours or less reduces energy costs. From this viewpoint, the solution treatment time is more preferably 2.7 hours or less, and particularly preferably 2.5 hours or less.

[0047] The aging temperature is preferably 450°C or higher and 550°C or lower. Aging at a temperature of 450°C or higher results in a structure in which Ni3Mo, Ni3Ti, and Ni3Al are sufficiently precipitated. From this viewpoint, the aging temperature is more preferably 460°C or higher, and particularly preferably 470°C or higher. Aging at a temperature of 550°C or lower suppresses the solid solution of alloying elements into the matrix. From this viewpoint, the aging temperature is more preferably 540°C or lower, and particularly preferably 530°C or lower.

[0048] The aging time is preferably 3.0 hours or more and 6.0 hours or less. Aging for 3.0 hours or more provides a structure in which Ni3Mo, Ni3Ti, and Ni3Al are sufficiently precipitated. From this viewpoint, the aging time is more preferably 3.3 hours or more, and particularly preferably 3.5 hours or more. Aging for 6.0 hours or less reduces energy costs. From this viewpoint, the aging time is more preferably 5.7 hours or less, and particularly preferably 5.5 hours or less.

[0049] [Hardness of the molded object after heat treatment] The Rockwell hardness HRC of the shaped article after the heat treatment is preferably 50 or more and 60 or less. A shaped article having a Rockwell hardness HRC of 50 or more has excellent strength. From this viewpoint, the Rockwell hardness HRC is particularly preferably 52 or more. A shaped article having a Rockwell hardness HRC of 60 or less has excellent toughness. From this viewpoint, the Rockwell hardness HRC is particularly preferably 58 or less. A method for measuring the Rockwell hardness HRC will be described later in the examples.

[0050] [Structure of the molded object after heat treatment] In the Fe-based alloy shaped article according to the present invention, the Laves phase derived from the Fe2Mo phase contained in the metal structure of the shaped article after heat treatment has a longitudinal length of less than 450 nm. A shaped article in which the longitudinal length of the Laves phase is less than 450 nm has excellent toughness. From this viewpoint, the longitudinal length of the Laves phase is more preferably 100 nm or less. A method for measuring the Laves phase will be described later in the Examples.

[0051] [XRD diffraction pattern of the molded object after heat treatment] In the diffraction pattern obtained by XRD measurement of the heat-treated shaped product, it is preferable that the peak intensity I1 at 2θ=36.5±1°, the peak intensity I2 at 2θ=37.8±1°, the peak intensity I3 at 2θ=41.3±1°, and the background peak intensity I4 at 2θ=35.0±1° satisfy the following formulas (1) and (2). An Fe-based alloy shaped product that satisfies these formulas (1) and (2) has excellent toughness. (I2-I4) / (I1-I4)≦1.5 (1) (I3-I4) / (I1-I4)≦1.5 (2)

[0052] Here, the peaks at 2θ=37.8±1° and 2θ=41.3±1° are both diffraction peaks due to the Laves phase derived from the Fe2Mo phase. The peak at 2θ=36.5±1° is a diffraction peak due to the precipitation strengthening phase. The precipitation strengthening phase is a phase precipitated due to an intermetallic compound (TiN) that contributes to improving the strength of the Fe-based alloy. Details of the XRD measurement will be described later in the examples.

[0053] From the viewpoint of improving toughness, it is more preferable that the above-mentioned peak strengths I1, I2, I3 and I4 satisfy the following formulas (3) and (4). (I2-I4) / (I1-I4)≦1.0 (3) (I3-I4) / (I1-I4)≦1.0 (4) EXAMPLES

[0054] The effects of the present invention will be clarified by the following examples, but the present invention should not be construed as being limited based on the description of these examples.

[0055] Raw materials having the compositions shown in Tables 1 and 2 below were prepared. Each raw material was heated by high-frequency induction in an alumina crucible to obtain a molten alloy. The molten alloy was dropped from a nozzle with a diameter of 5 mm formed at the bottom of the crucible, and high-pressure argon gas was sprayed onto it. The molten metal was atomized and quenched by this spray, forming a powder. This powder was classified so that the diameter of each particle was 63 μm or less, and an Fe-based alloy powder was obtained.

[0056] Using the obtained Fe-based alloy powder as material, a three-dimensional additive manufacturing device (product name "EOS-M280") was used to manufacture each of the shaped objects (unheat-treated). Each of the unheat-treated shaped objects was subjected to heat treatment under the conditions shown in Tables 1 and 2 below to manufacture the Fe-based alloy shaped objects of Examples 1-22 and Comparative Examples 1-11.

[0057] [Hardness measurement] A 10mm square test piece (10x10x10mm) was prepared, and a basic load of 10kgf was applied to the test surface of the test piece using an indenter with a diamond steel ball with a tip radius of 0.2mm. Next, a load of 110kgf, which is the basic load plus the test load of 100kgf, was applied to the test piece, causing plastic deformation of the test piece. Next, the load was returned to the standard load of 10kgf, and the depth of the permanent indentation from the standard surface was measured. From this depth, the Rockwell hardness HRC was calculated using a conversion formula. Measurements were performed before and after heat treatment. The results are shown in Tables 1 and 2 below as "Hardness (HRC)".

[0058] [Textural observation] The structure was observed by either method (A) or (B) below to determine the longitudinal length of the Laves phase derived from the Fe2Mo phase. The results obtained for the molded objects before and after the heat treatment are shown in Tables 1 and 2 below as "Laves phase major axis (nm)". Method (A): A thin-film test piece was prepared by FIB (focused ion beam) processing. This test piece was observed with a transmission electron microscope (TEM). The composition of the compound was identified at 10 randomly selected locations (each location was an area of ​​2 μm × 2 μm), and the longitudinal length of the Laves phase derived from the Fe2Mo phase was measured and the average value was calculated. Method (B): Each molded object was reacted with sulfosalicylic acid to produce an extraction residue, which was then observed under a transmission electron microscope (TEM). The composition of the compound was identified at 10 randomly selected locations (each location was an area of ​​2 μm × 2 μm), and the longitudinal length of the Laves phase derived from the Fe2Mo phase was measured and the average value was calculated.

[0059] A transmission electron microscope image obtained in Example 15 after the heat treatment is shown in Figure 1. A transmission electron microscope image obtained in Comparative Example 1 after the heat treatment is shown in Figure 2. In Figures 1 and 2, the black dots or black areas are the Laves phase derived from the Fe2Mo phase.

[0060] [XRD measurement] The shaped objects of the examples and comparative examples were each reacted with sulfosalicylic acid to produce extraction residues, which were then subjected to XRD measurement under the following conditions using an X-ray diffractometer (manufactured by Rigaku Corporation under the trade name "RINT-2500"). Source: CuKα 2θ:20-80°

[0061] The diffraction pattern obtained in Example 15 after the heat treatment is shown in Figure 3. The diffraction pattern obtained in Comparative Example 1 after the heat treatment is shown in Figure 4. In Figures 3 and 4, the black triangles indicate peaks due to the Laves phase derived from the Fe2Mo phase, the white triangles indicate peaks due to Ti compounds, and the black squares indicate peaks due to the precipitation strengthening phase (TiN).

[0062] From the obtained diffraction pattern, the peak intensity I1 at 2θ=36.5±1°, the peak intensity I2 at 2θ=37.8±1°, the peak intensity I3 at 2θ=41.3±1°, and the background peak intensity I4 at 2θ=35.0±1° were obtained, and the ratios R(1) and R(2) were calculated using the following formulas. The results obtained for the shaped object before and after the heat treatment are shown in Tables 1 and 2 below. R(1) = (I2 - I4) / (I1 - I4) R(2)=(I3-I4) / (I1-I4)

[0063] [Martensitic transformation start temperature] A test piece with a diameter of 3 mm and length of 10 mm was taken from the molded object before heat treatment. A hole with a diameter of 2 mm and a depth of 2 mm for thermocouple welding was machined in this test piece. This test piece was placed in a Formaster testing machine and heated at a rate of 10°C / sec., held at a maximum temperature of 1000°C for 10 minutes, and then cooled at a rate of 200°C / sec. The mutation point observed during cooling was determined as the martensitic transformation start temperature. The results are shown in Tables 1 and 2 below as "Ms point (°C)".

[0064] [Room temperature tensile properties] A JIS No. 14A φ5 test piece (φ5 × GL25mm) was prepared and subjected to a tensile test at a temperature of 20°C in accordance with JIS regulations. The maximum tensile stress σ (σ = measurement load F / cross-sectional area S) applied during the test is the tensile strength. The load and elongation were plotted on a graph, and a straight line was drawn parallel to the elastic region, offset by 0.2% of the gauge length, and the stress at the intersection with the load curve was calculated as the 0.2% yield strength. The elongation Z was calculated based on the following formula. Z = (Lf-L0) / L0 x 100 In this formula, L0 is the initial gauge length and Lf is the gauge length at break. The results are shown in Tables 1 and 2 below as "Tensile Strength (MPa)".

[0065] [Charpy impact properties] JIS No. 4 test piece 2 mm V-notch test piece (10 x 10 x L55 mm) was prepared and Charpy impact test was carried out at 20℃ in accordance with JIS regulations. The hammer was swung down using the same principle as a pendulum, and after destroying the test piece, the height of the hammer was measured when it was pushed out in the opposite direction by its own momentum. This result was called the "Charpy impact value (J / mm 2 )" in Tables 1 and 2 below.

[0066] [rating] Each molded object after heat treatment was ranked from 1 to 4 based on the following criteria. (Rating 1) Tensile strength: 1700MPa or more Charpy impact value: 20.0J / mm 2 End (Rating 2) Tensile strength: 1700MPa or more Charpy impact value: 15.0J / mm 2 More than 20.0J / mm 2 less than (Rating 3) Tensile strength: less than 1700MPa Charpy impact value: 10.0J / mm 2 More than 15.0J / mm 2 less than (Rating 4) Tensile strength: less than 1700MPa Charpy impact value: 10.0J / mm 2 less than

[0067] [Table 1]

[0068] [Table 2]

[0069] [Footnotes to Tables 1 and 2] The symbol UM in the component composition column indicates that the amount is below the limit of quantification (measured by ICP-MS (inductively coupled plasma mass spectrometry)). The symbol "-" in the solution heat treatment temperature column indicates that the solution heat treatment was not performed. The symbol "-" in the solution heat treatment time column indicates that the solution heat treatment was not performed.

[0070] As shown in Tables 1 and 2, the objects of the respective Examples were excellent in the overall evaluation. From these results, the superiority of the present invention is clear. [Industrial Applicability]

[0071] The Fe-based alloy shaped article according to the present invention can also be obtained by a 3D printer of the type in which powder is sprayed from a nozzle.The shaped article can also be obtained by a laser coating method of the type in which powder is sprayed from a nozzle.

Claims

1. the material is an Fe-based alloy containing 0.0% by mass or more and 0.5% by mass or less of Co, 2.0% by mass or more and 14.9% by mass or less of Mo, 3.1% by mass or more and 25.1% by mass or less of Ni, 0.5% by mass or more and 5.1% by mass or less of Ti, and 0.09% by mass or more and 3.00% by mass or less of Al, with the balance being Fe and unavoidable impurities, and containing a precipitation strengthening phase derived from an intermetallic compound TiN; In the metal structure, Fe 2 The length of the Laves phase derived from the Mo phase in the longitudinal direction is less than 450 nm, In the diffraction pattern obtained by XRD measurement using CuKα as a radiation source, the peak intensity I at 2θ = 36.5 ± 1 ° 1 and the peak intensity I at 2θ=37.8±1° 2 and the peak intensity I at 2θ=41.3±1° 3 and the intensity I of the background peak at 2θ=35.0±1° 4 and an Fe-based alloy shaped object, which satisfies the following formulas (1) and (2). (I 2 -I 4 ) / (I 1 -I 4 )≦1.5 (1) (I 3 -I 4 ) / (I 1 -I 4 )≦1.5 (2)

2. 2. The Fe-based alloy shaped article according to claim 1, wherein the Laves phase has a longitudinal length of less than 100 nm.

3. In the diffraction pattern obtained by XRD measurement using CuKα as a radiation source, the peak intensity I at 2θ = 36.5 ± 1 ° 1 and the peak intensity I at 2θ=37.8±1° 2 and the peak intensity I at 2θ=41.3±1° 3 and the intensity I of the background peak at 2θ=35.0±1° 4 The Fe-based alloy shaped article according to claim 1 or 2, wherein the following formulas (3) and (4) are satisfied. (I 2 -I 4 ) / (I 1 -I 4 )≦1.0 (3) (I 3 -I 4 ) / (I 1 -I 4 )≦1.0 (4)

4. The Fe-based alloy shaped article according to claim 1 , wherein the Fe-based alloy has a Co content of less than 0.35 mass %.

Citation Information

Patent Citations

  • Novel nitride-reinforced martensite heat-resisting steel

    CN102758141A

  • Method of manufacturing maraging steel strip having high fatigue strength

    JP2008185183A

  • Maraging steel

    JP2013253277A

  • Fe-BASED METAL POWDER FOR MOLDING

    JP2019077937A

  • Additive manufacturing of objects from maraging steel powder

    JP2021512999A